An Asian Study of the Monetary and Banking Liquidity Impact on Share Prices - Tin-fah Chungand; Mohamed Ariff (The International Journal of Banking and Finance, 2016)
Following Friedman’s hypothesis that credit expansion will follow a monetary and liquidity binge, we used data from 1968-2012 in Asia (Japan, Korea, China and India) to explore this hypothesis. Our results from applying single and cointegration equations provided empirical support to the above hypothesis. This liquidity binge following a monetary impact on share prices was tested in four major Asian economies. As per the theory’s prediction, monetary changes led to a positive banking liquidity effect, based on lengthy quarterly equations using the dynamic OLS method. We also showed that banking liquidity changes have a significant positive effect on share prices, after controlling for the effects of earning changes, regime changes and the global financial crisis. These findings, obtained after solutions to serious econometric issues in existing studies, appear to provide a clear verification of theory on the monetary effect on banking liquidity and banking liquidity’s effect on share prices.